Application of Article 6 of the European Convention of Human Rights in Enforcement Proceedings - Dalia Višinskytė; Mykolas Kirkutis; Remigijus Jokubauskas; Vigintas Višinskis (LeXonomica, 2021)
The application of procedural guarantees of the right to a fair trial is significant for effective legal defence. Certain element of the right to a fair trial are applicable in enforcement proceedings, such the requirement for reasonable length of enforcement proceedings, cooperation between the parties, the principle of adversarial proceedings. Since enforcement proceedings are an integral part of litigation in the court, states may be liable for a failure to ensure effective enforcement proceedings.Povzetek. Uporaba procesnih jamstev pravice do poštenega sojenja je pomembna za učinkovito pravno varstvo. Nekateri elementi pravice do poštenega sojenja se uporabljajo v izvršilnih postopkih, kot so zahteva po razumnem trajanju izvršilnega postopka, sodelovanje med strankami in načelo kontradiktornosti. Ker je izvršilni postopek sestavni del pravdnega postopka pred sodiščem, so lahko države odgovorne, če ne zagotovijo učinkovitega izvršilnega postopka.